The New School in Chile: The Relationship with Educational Organizations and with the Configuration of a Democratic Educational Public System [a Escola Nova No Chile: Relação Com as Organizações Docentes E Com a Conformação de Um Sistema Educativo Democrático] [la Escuela Nueva en Chile: Relación Con Las Organizaciones Docentes y Con la Conformación de Un Sistema Educativo Público Democrático] - Caiceo-Escudero, J (Universidade Estadual de Maringa, 2021)
The influence that the American, educator John Dewey,-principal representative of the ‘New School’ in Chile-has had on education systems to level world is vastly known; repeatedly visited directly some countries, as Japan, China, Turkey and Soviet Union; to Spain became especially their educational pragmatism since the beginning of the 20th century, in the translation of several of his works, which had an influence on the so-called ‘New Education’; he was also positively received in Mexico-where was twice-, Colombia and Brazil. Indeed in his homeland was widely received, both as pragmatic philosopher and educationalist. His democratizer view, created by the observation of the situation in his country, he wanted it to expand to other continents; increasing the scholarship in different countries, according to him, it will reinforce their democratic system. This article has two objectives: (i) identify major teachers groups existing in the first three decades of the 20th century in Chile and point to its main exponents and (ii) analyzed the contribution there of in the diffusion of the pedagogy of Dewey and the influence they had on changes in the school system, especially in the promotion of new publics politics that each one of them realized during the designated period. © 2021, Universidade Estadual de Maringa. All rights reserved.